THE EFFECT OF QUALITY OF WORK LIFE ON WORK MOTIVATION OF CRIMINAL UNIT MEMBERS AT SOUTH JAKARTA METROPOLITAN POLICE DISTRICT - Alfred Sabungan Banjar Nahor (Pusat Penelitian dan Pengembangan Polri, 2022)
This study aims to determine whether there is an influence between the quality of work life on the work motivation of members of the South Jakarta Metropolitan Police Criminal Investigation Unit. This study uses a quantitative approach using a survey method, where the number of respondents in this study consisted of 134 members of the South Jakarta Metropolitan Police Criminal Investigation Unit. Sampling using the saturated sample method where the entire population is sampled in the study. The data collection technique used in this research is to use a questionnaire distributed to respondents. From the results of the study, it was found that (1) there is a very strong relationship between the quality of work life and the work motivation of members of the South Jakarta Metropolitan Police Criminal Investigation Unit, where the relationship between the two variables is positive; (2) the percentage of the influence of the quality of work life which consists of supervision, wages and incentives, work as a reward, challenging work, interesting work, and working environment conditions simultaneously on the work motivation of members of the South Jakarta Metropolitan Police Criminal Investigation Unit is 82.1% .